Adaptive DSP algorithm for calibrating drop size distribution rain gauges - Kasparis, Takis; Lane, John E.; McFarquhar, Greg M. (My University, 1997)
The calibration of impact disdrometers has traditionally been a tedious process, whereby known diameter single water droplets are generated and allowed to fall from a height of 10 meters or more in order to obtain terminal velocity. An alternate method of calibration is proposed which eliminates the need of a single drop generator and associated drop shaft. The strategy behind this technique is to use an accumulation rain measurement instrument, such as a tipping bucket rain gauge, to provide a known signal for the purpose of training an adaptive calibration algorithm. The reference signal to this digital signal processing algorithm is the output of the impact disdrometer which is preprocessed by an impulse amplitude estimation algorithm. This calibration technique has been evaluated using data from UCF's Acoustic Rain Gauge Array, which estimates raindrop size distributions (1 mm drop diameter or more) by digitally sampling the acoustic signal from an array of acoustic impact sensors. This calibration technique should be applicable for use with other impact disdrometers.
Keywords: Calibration; Algorithms; Estimation; Digital signal processing